Corporate political activity of major food companies in Thailand: an assessment and policy recommendations - Nongnuch Jaichuen; Sirinya Phulkerd; Nisachol Certthkrikul; Gary Sacks; Viroj Tangcharoensathien (BMC, 2018)
Abstract Background The food industry can influence individual and population level food consumption behaviours, shape public preferences and interfere with government policy on obesity prevention and NCDs. This paper identifies the Corporate Political Activity (CPA) of major food companies in Thailand which relate to obesity and NCDs. Methods Using the INFORMAS framework to classify CPA, we reviewed publicly available information by 12 food companies between August 2011 and July 2016 in order to identify, analyse and classify the CPA contents. Semi-structured interviews with 17 key stakeholders who are experts in this field supplemented evidence from the document review. Data analysis applied a thematic approach. Results Food industry in Thailand applied a variety of CPA strategies and practices. The two most common strategies were constituency building and information and messaging. Conclusion The diverse range of CPA strategies which influence government policy and public opinion can undermine efforts to prevent obesity and diet-related NCDs. We recommend systematic monitoring of their CPA, strengthening mechanisms to hold the food industry accountable for their role in protecting and promoting the nutrition and health of the population, introducing mandatory registration of lobbyists, mandatory disclosure of political donations, and stronger oversight of conflicts of interest among the government actors.